Heat shock protein 90α in thymic epithelial tumors and non-thymomatous myasthenia gravis. (1st January 2020) - Thanner, Jürgen; Bekos, Christine; Veraar, Cecilia; Janik, Stefan; Laggner, Maria; Boehm, Panja M; Schiefer, Ana-Iris; Müllauer, Leonhard; Klepetko, Walter; Ankersmit, Hendrik Jan; Moser, Bernhard
ABSTRACT: Background: Thymic epithelial tumors (TETs) are rare malignancies with unique association to the autoimmune disease myasthenia gravis (MG). Heat shock proteins (HSPs) harbor great potential as cancer biomarkers and HSP inhibitors approach clinical cancer therapy. Methods: To explore HSP pathophysiology, we assessed sera (immunoassays) and tissues (immunohistochemistry) of TETs (and thymic tissues) for HSP27, phosphorylated (p)HSP27, HSP70 and HSP90α expression in 114 TETs and 26 non-thymomatous MG patients undergoing extended thymectomy. Results: Serum concentrations of HSP90α were significantly increased in patients with thymic carcinomas, thymomas, thymic neuroendocrine tumors and non-thymomatous MG compared to patients who underwent thymectomy revealing regular thymic morphology or controls. In thymoma patients, high serum HSP90α represented a significantly worse prognostic factor for free-from-recurrence, and complete tumor resection led to decreased levels. The expression of HSP90 in nuclei and cytoplasm of tumor cells and non-neoplastic lymphocytes varied with WHO histological subtype. HSP90 was expressed in centroblasts of thymic germinal centers in MG patients. Higher pHSP27 serum concentrations were observed in seropositive MG and those not treated with steroids. Conclusions: HSP data suggest high potential for HSPs as TET cancer biomarkers or as candidates for targeted therapy. Caution is warranted in TET patients with associated MG overexpressing HSPs.